No evidence of MMR induced trained immunity to prevent SARS COV2: results from a multi-centre RCT - Delany-Moretlwe, Sinead; Dehbi, Hakim-Moulay; Sikazwe, Izukanji; Kyei, George; Koram, Kwadwo; Dubberke, Erik; Mwelase, Noluthando; Hague, Dominic; Bekker, Linda-Gail; Yun, Linda; Nel, Annalene; Toit, Leon du; et al. (Frontiers in Immunology, 2025)
BackgroundMeasles-containing vaccines (MCV), by training innate immune cells, are hypothesized to prevent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and coronavirus disease 2019 (COVID-19).MethodsIn this international, double-blind, placebo-controlled trial, we randomly assigned adults, 18 years and older, to receive MCV or saline. The primary outcome was polymerase chain reaction (PCR) confirmed symptomatic COVID-19, up to 60 days after intervention. Secondary outcomes were PCR-confirmed symptomatic COVID-19 and serologically confirmed SARS-CoV-2 infection, up to 150 days after intervention.ResultsOf 3411 randomised participants, the modified intention-to-treat population included 1607 in the MCV and 1545 in the saline group. The estimated risk of symptomatic COVID-19 by 60 days was 1.5% in the MCV and 1.2% in the saline group (risk difference, 0.3 percentage points, 95% CI, -0.5 to 1.1; p=0.52). At 150 days, these percentages were 4.1% (65/1585) and 4.1% (64/1544) in the MCV and saline groups, respectively (risk difference, 0.04 percentage points, 95% CI, -1.4 to 1.3; p=0.95). Based on serology results available at 0 and 150 days, 10.6% (100/945) of participants in the MCV and 10.3% (98/951) in the saline group had infection with SARS-CoV-2 over the course of the trial (risk difference, 0.3 percentage points, 95% CI, -2.6 to 3.1; p=0.84). Three patients were hospitalised with COVID-19 disease in the MCV and one in the saline group.ConclusionsAdministering MCVs to stimulate trained immunity did not prevent COVID-19 or SARS-CoV2 infection. Stimulating trained immunity might not be useful for preventing respiratory illness during future pandemics.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT04333732.